PAI Learning Evaluation Management Based on Authentic Assessment - Shohir Shohir (Classroom: Journal of Islamic Education, 2025)
Changes in education in Indonesia take the form of a new curriculum which functions as a complement to the previous curriculum, namely KTSP. This study method is to use library research which will be analyzed and concluded. The results of this research are to discuss the meaning of authentic assessment, characteristics of authentic assessment, comparison of authentic and non-authentic assessment, principles of authentic assessment, techniques and instruments, components of authentic assessment, as well as problems of implementing authentic assessment in schools and universities. Conclusion: Authentic assessment techniques pay attention to 3 things, namely affective, cognitive and psychomotor competencies. The components of authentic assessment that need to be considered are the preparation of authentic assignments and authentic assessment rubrics. Meanwhile, Probematics implements authentic assessment in schools and universities, each school and college has different obstacles.